2007
DOI: 10.1080/14017430701283864
|View full text |Cite
|
Sign up to set email alerts
|

Single versus sequential saphenous vein grafting of the circumflex system: A flowmetric study

Abstract: SeqSV-CABG showed higher TTF flows, with no incremental risk for perioperative morbidity. Higher flows and graft flow reserve may allow lower treatment failure at mid-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…Increased graft flow rate has been associated with decreased SVG intimal proliferation (15). Some series have reported better TTF measurements (16,17) or patency (15,18) results with sequential grafting strategy compared to single graft while others have not (19)(20)(21). A meta-analysis of 12 studies comparing the patency of sequential and individual vein grafts concluded that the mid-and long-term patency of sequential vein grafts were superior to single vein grafts (14).…”
Section: Coronary Graft Flow Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased graft flow rate has been associated with decreased SVG intimal proliferation (15). Some series have reported better TTF measurements (16,17) or patency (15,18) results with sequential grafting strategy compared to single graft while others have not (19)(20)(21). A meta-analysis of 12 studies comparing the patency of sequential and individual vein grafts concluded that the mid-and long-term patency of sequential vein grafts were superior to single vein grafts (14).…”
Section: Coronary Graft Flow Measurementmentioning
confidence: 99%
“…Conversely, in the off-pump group: A) local coronary occlusions of short duration probably are unable to trigger a "vasodilation effect"; B) vasopressors used to stabilize hemodynamics during off-pump surgery can constrict the coronary vascular bed; and 3) coronary snaring has been associated with microthrombosis, atherosclerotic plaque rupture, focal endothelial denudation, distal embolization, and injury to target vessel branches (26). Intracoronary shunting may protect against back wall suturing, another cause of early graft failure, however it is also associated with more technically demanding anastomoses and intimal injury (17). In addition to off-pump surgery, female gender was identified as a predictor of lower coronary graft TTF measurements.…”
Section: Coronary Graft Flow Measurementmentioning
confidence: 99%
“…Therefore TTF may help us to understand subtle physiological differences between arterial and venous grafts, which can then have an impact on the fate of the grafts. It has been demonstrated that the principal determinant of the patency rate of CABG in the late postoperative period is the flow rate throughout the graft [21]: Faulkner reported a strict association between an increased flow rate and a less intimal proliferation [8]; Rittgers demonstrated a reverse relationship between the flow rate and intimal proliferation [22]. The better TTF and GFR results of RA grafts may be the explanation of a higher patency rate compared to SV, already reported by some Authors [23].…”
Section: Discussionmentioning
confidence: 99%
“…TTFM has been reported as important for determining the success of grafts during surgery [22] and for predicting the risk of graft failure after surgery [21], making TTFM the most widely used method of intraoperative graft quality control in patients undergoing CABG surgery [3][4][5][6][7][8]. Prior to this study, however, the perioperative factors affecting TTFM during CABG surgery had not been determined, making this study one of the first to assess perioperative factors affecting flow measurements in graft vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Transit-time flow measurement (TTFM), which utilizes ultrasound to measure flow velocity in blood vessels, is frequently used for intraoperative assessment of graft quality in patients undergoing coronary artery bypass graft (CABG) surgery [3][4][5][6][7][8]. TTFM is a noninvasive, easy-to-use method of measuring graft flow velocity in real time, does not require complex equipment, and provides numerical results [9,10].…”
Section: Introductionmentioning
confidence: 99%